Peer-to-Peer for Virtual Home Environments - Loeser, Chris; Müller, Wolfgang; Berger, Franz; Eikerling, Heinz-Josef (Proceedings of HICCS-36)
This pap er presents an approach to extend OSGi server based home networks with JXTA's p eer-to- p eer (P2P) technology to a multi-server home envi- ronment connecting multiple private home networks to one true virtual environment for communication, media sharing/exchange, and distributed device con- trol. We elab orate on the basic integration metho d- ology and extend it to a general, security preserv- ing, architectural concept based on a two level inte- gration concept for inhome and interhome networks. The integration is achieved through additional OSGi services for the management of virtual devices, p eer- to-p eer communication, and authentication. The ex- ample of a Quality of Service based video streaming management demonstrates one of the p otential ad- vanced application for which p eer-to-p eer can b e used in addition.